Dermatoses in geriatric patients - Dagmaris Albear de la Torre; Mayelin Valdivia Ferreira; Ivelin Valle-Yanes; Mayli Barbara del Rio Ysla; Susana María Hernández-Rodríguez; Yulexi Gómez Águila (Revista Cubana de Medicina Militar)
Introduction: Skin aging is part of an endogenous and exogenous deterioration process in cells. The degenerative and metabolic changes that occur make this population vulnerable to dermatological conditions. Objective: To define frequent skin diseases in geriatric patients, seen in a dermatology office. Methods: A cross-sectional descriptive observational investigation was carried out in geriatric patients treated in the Dermatology consultation at the Policlínicade losCombatientes, Ciego de Ávila, in the period from January to December 2019. The study series consisted of 144 older adults. The variables studied were: age, sex, skin color, skin phototypes, dermatological conditions, location and associated morbidities. Results: Older adults between 70 and 79 years old (53,5 %), male (50,7 %) predominated. 63,9 % of the patients had skin phototype III. The most frequent dermatoses were senile purpura (34 %) and seborrheic keratosis (25 %), older adults with white skin were more affected (69,4 %). Dermatoses on the face and extremities were the most frequent (53,5 % and 17,4 %). 46,6 % of the patients suffered from disorders of the osteomyoarticular system, followed by arterial hypertension (18,5 %) and diabetes mellitus (12,6 %). Conclusions: Older male adults from 70 to 79 years old, with skin phototype III predominated. Senile purpura, seborrheic keratosis, and xerosis were common conditions in white-skinned elderly. Lesions limited to the face were highlighted.